Mucormycosis in COVID-19- A burgeoning epidemic in the ongoing pandemic - Mahak Lamba; Deepak Bhagchandani; Ambuj Yadav; Virendra Atam (International Journal of Health and Clinical Research, 2021)
Introduction: Along with COVID-19, India is also experiencing an outbreak of mucormycosis, a deadly fungal infection, which is affecting thousands of COVID-19 patients. Also known as black fungus, this disease is caused by opportunistic fungi in the Mucorales family. Material and Method: This is a retrospective study among mucormycosis patients, admitted to tertiary care teaching centre over a period of 3 months. These cases were admitted for the management of mucormycosis. They were assessed and treated by the relevant specialties at various time points, which included internists, infection disease specialists, intensivists and otolaryngologists. Data pertaining to demographics, clinical features, co-morbidities, laboratory investigations, histopathology, management and outcomes were collected. Results: In our study, 461 patients diagnosed with mucormycosis were included. Male were predominant (63.3%) and the mean age was 53 ± 9.7 years. All patients initially presented with nasal congestion with or without discharge consistent with sinusitis. The majority of patients with mucormycosis experienced a non-descript localised or generalised headache. Symptoms include diplopia, visual disturbances, facial weakness or numbness. Features of ophthalmoplegia, proptosis and long-tract signs were also observed in a proportion of patients. Imaging investigations revealed that most of the patients had features of maxillary sinusitits. Based on microbiology and/or histopathology, all subjects had features of mucormycosis. A small proportion had additional co-infection with aspergillosis and bacteria. Conclusion: The incidence of mucormycosis in the setting of the COVID-19 pandemic is likely to rise and result in significant morbidity and mortality. Physicians caring for severely ill patients with COVID-19 and concomitant poorly controlled diabetes should have a high index of suspicion of mucormycosis, especially if corticosteroids are used during the course of disease.